Community Empowerment Through Business Strategy Training, OSS-RBA Legality, And Capital Access For MSMEs In Gudang Kahuripan Village - Yayan Sugiarto; Surya Adtya Wahyono; Dewi Fitriani; Rd. Intan Media Ratna Puri; Dadi Indra Permana (Inaba of Community Services Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) are backbone of the national economy, but its development often constrained problem structural, legality, and literacy financial activities​ Devotion to the Community Services aim For increase capacity entrepreneurship students and the community in the Lembang area through training establishment of MSMEs, management legality, and expansion access capitalization. The method used is Experiential Learning that integrates theory with practice live, including interactive workshops, simulations Online Single Submission Risk-Based Approach (OSS-RBA) system, up to market implementation through MSME bazaar activities. Evaluation results quantitative show improvement significant to understanding participants, especially in the aspect step start business (up 47%) and access capitalization (up 42%). In general, practical, ownership Business Identification Number (Nomor Induk Berusaha) increase from 57% to 81% post-training. In addition, the bazaar activities were successful push business unit activation participant from 53% to 78%. Discussion results activity confirm that simulation practice direct effective mitigates obstacle psychological related complexity bureaucracy licensing. In conclusion, synergy between education legality, motivation through bazaars and literacy capital capable transforming participants' mindsets from informal businesses become planned formal business. This program give contribution real for strengthening ecosystem entrepreneurship local and independent economy community in Gudang Kahuripan Village